MODELS OF LEARNING RESOURCE TECHNOLOGIES WATER FOR "DRY" FILTERS (Municipal economy of cities. Series: «Economy science», 2013)
Clearing of highways surface rain drains in the conditions of the northwest application is perspective with multilayered filters of a small thickness. For an overall performance substantiation thin layer filtering is used the theory «sorption dynamic» device. Optimum for application sorption materials are considered.